(untitled) (Research, Society and Development, 2021)
Objective: to analyze the sociodemographic and health profile of the elderly assisted by home care services. Methodology: this is an integrative literature review. data collection and search for studies took place during the month of october 2020, in the following databases, latin american and caribbean literature in health sciences (lilacs) and database in nursing (bdenf) consulted by the virtual library of health (vhl). Results: the articles analyzed report the sociodemographic profile of elderly users in home care and clinical and epidemiological characterization of elderly users in home care. elderly people in ad are mostly women, married and/or single and with low education (incomplete elementary education) who live with chronic diseases such as alzheimer’s, diabetes mellitus, copd and neoplasms. Among the most frequent comorbidities among users is sah, with cva being the main disease for admission to home care. Conclusion: through knowledge of the health profile of elderly people in ad observed in this integrative review, it is possible to collaborate with the planning of care strategies related to this population, aimed at a more comprehensive and resolute care.